Age chronology based on U/Th ages, bomb pulse 14C data and year of collection (2012) of Stalagmite GL-S1 from the Golgotha Cave in southwest Western Australia - Treble, Pauline C; Baker, Andy; Abram, Nerilie J; Hellstrom, John C; Crawford, Jagoda; Gagan, Michael K; Borsato, Andrea; Griffiths, Alan D; Bajo, Petra; Markowska, Monika; Priestley, Stacey; Hankin, Stuart I; et al. (In: Treble, PC et al. (2022): Golgotha Cave stalagmite records 1 ka [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.941440, 2022)
Stalagmite GL-S1 chronology in ka CE based on U/Th ages, bomb pulse 14C data and year of collection (2005). Treble et al. (2022) used 17th percentile age-depth model.
Keywords: Golgotha Cave; Last millennium; speleothem; stalagmite; Western Australia